Status and determinants of multi-dimensional poverty in Wolaita Sodo Town, southern Ethiopia - Esrael, Eshetu; Worku, Asrat; Cucchi, Carlo; Belay, Abrham; Recha, John W.M.; Tafesse, Alula (Elsevier, 2025)
Multi-dimensional poverty remains a staggering problem in Ethiopia, especially among urban households. Despite its widespread recognition, there is a dearth of comprehensive studies that specifically examine the status and determinants of multi-dimensional poverty, especially in urban settings. This study focused on an in-depth examination of the status and determinants of multi-dimensional poverty among urban households in Wolaita Sodo, Ethiopia. Cross-sectional data was collected from 240 randomly selected urban households. Descriptive statistics and logistic regression econometric models were utilized to analyze the data. More than half of the sampled respondents are classified as multi-dimensionally poor. The intensity of poverty was measured at 65.1 %, while the adjusted headcount ratio stood at 33.95 %. In terms of dimensions, the living standards dimension emerged as the primary contributor to overall multidimensional poverty, accounting for 40.3 % of the total followed by the education dimension (32.3 %) and the health dimension (26.5 %). Among the seven indicators used in the Multidimensional Poverty Index (MPI), school attendance (17.1 %) and food insufficiency (22.4 %) indicators made the highest relative contributions to the overall multidimensional poverty index. The remittance (P < 0.01), employment status (P < 0.01), age of household head (P < 0.10), household size (P < 0.01), and expenditure (P < 0.01) significantly influence multidimensional poverty. To alleviate the elevated levels of multidimensional poverty in the study area, it is advisable to target households with larger family members, target households with access to remittance, enhance access to quality education, support aged household heads and create conducive environment for investors to start medium- and large-scale industries for better employment opportunity.